A lei 13.415/2017 do Ensino Médio e sua relação com as orientações e recomendações do Banco Mundial para o Ensino Médio - Godoi, Wellington da Silva (2022)
High School is historically characterized as emblematic and controversial, whether in its offer, curricular organization, identity or financing. In the last decades it has been the target of disputes and debates involving several sectors of society. There have been numerous attempts, reformulations, bills, and curricular guidelines discussed and debated with the purpose of changing the model of High School. Until in 2017, under the Michel Temer government, through Provisional Measure 746/2016, which later became Law 13.415/2017, High School was restructured. This research has as its object of investigation the so-called New High School. Moreover, the research started from the following problem: is there a relationship between the New High School (law 13.415/2017) with the guidelines and recommendations of the World Bank? The World Bank is understood as a Multilateral International Organization that arose after World War II to assist in the reconstruction and economic and political reordering of countries affected by the war. However, as time went by and mediated by the historical, economic and political conditions of the capitalist system, it started to elaborate guidelines and recommendations for the social areas of the peripheral countries, among them Brazil. In this sense, the World Bank produces documents, reports and statistics about the education systems and creates guidelines and recommendations. Moreover, the World Bank continues to act as a provider of agreements involving loans, which are accompanied by financial and ideological counterparts and conditionalities. This research is based on the historical-dialectical materialism as a theoretical-methodological foundation. The research is documental and bibliographical in nature, analyzing reports and documents of the Bank, among them: Competence and Employment: an Agenda for Youth (2018); and the Loan Agreement and the Support Program for the Implementation of the New High School. In relation to High School, laws, draft laws, National Curriculum Guidelines for High School and law 13415/2017 itself are analyzed, establishing relationships with the Bank's documents. The research covered three moments: the first is the contextualization of Brazilian High School, analyzing the historical path of disputes and debates until the law 13.415/2017.The second moment, is to analyze the historical, political and ideological trajectory of the World Bank. Last but not least, it was analyzed the guidelines and recommendations for High School in the World Bank documents and in the High School Implementation Support Program relating them to the National Curricular Guidelines for High School and Law 13.415/15. It is concluded that there is a relationship between the guidelines and recommendations of the Bank and the New High School, in both models of high school it is possible to find in common: flexibility of the curriculum, based on skills and abilities; partnerships with the private sector; training back to productivity and the labor market; training itineraries; increased workload, etc